Efficiency of solarization and biofumigation on tomato bacterial wilt control in the field - Baptista, Mírian Josefina; Junior, Fabio Bueno dos Reis; Xavier, Gustavo Ribeiro; Alcântara, Camila de; Oliveira, Antonio Régis de; Souza, Ronessa Bartolomeu; Lopes, Carlos Alberto (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the efficiency of soil solarization and biofumigation under diverse application conditions, on tomato bacterial wilt control in the field and their effects on soil chemical and microbiological properties. The soil was evaluated after two, four and six months of solarization and biofumigation with 2 and 5% of chicken litter amendment. The study was carried out in a field highly infested with Ralstonia solanacearum. There was no interaction between solarization and biofumigation on bacterial wilt control. Only solarization for four months and biofumigation with 5% chicken litter amendment reduced significantly the incidence of tomato bacterial wilt. Soil solarization caused reduction in soil Na and K content, only in the 4th and 6th months of application, and had no significant effect on other soil chemical properties, but reduced microbial biomass and microbial respiration. Nevertheless, microbial respiration increased 60 days after solarization period. Biofumigation increased soil nutrient levels, microbial biomass and respiration. Soil solarization for four months and biofumigation with 5% chicken litter amendment are efficient in soil treatment for reduction of tomato bacterial wilt incidence in highly infested areas.